An analysis of offenders referred for forensic observation in Limpopo from January 2005 to December 2006 - Ndala, Monicah (University of Limpopo (Medunsa Campus), 2009)
INTRODUCTION There seems to be an increase in the crime rate in South Africa with substantial regional variations as the crime rate and trends differ between provinces and cities with Limpopo being hailed the safest province. In South Africa a defendant in a criminal case can be referred for 30 days of psychiatric observation at any stage of the process. This is to assess whether the accused has a mental illness or defect in terms of the Criminal Procedure Act (Act 51 of 1977) Section 79(2) as amended in the Criminal Matters Amendment Act 1998 (Act 68 of 1998). There is a perception that most of the accused referred for psychiatric observation are known Mental Health Care Users. OBJECTIVE To establish a profile of offenders referred for psychiatric observation in Limpopo from January 2005 to December 2006. METHOD A descriptive retrospective study was done. Information was collected from the computer database available in the Psychiatry Department Polokwane/Mankweng Hospital Complex. The study population consisted of all 678 reports referred by the courts for observation during the period January 2005 to December 2006. Data were analyzed and summarized using frequencies and percentages. RESULTS Over 80% (85% in 2005, 86% in 2006) of the observations were done on an outpatient basis. Of the offenders referred 94% were males. The majority was in the 21-30 age groups. Mopani District had the highest number of referrals and the majority of them were found to be mentally ill. Of the offenders sent for observation in 2005 and 2006, 53% had previous psychiatric contact versus 47% with no previous psychiatric contact. • Of the offenders found fit to stand trial 41% had previous psychiatric contact. • Of those found not fit to stand trial 67% were known Mental Health Care Users. • Of those found not fit to stand trial 33% had never received any formal psychiatric treatment and entered the system through the criminal justice system. Most common mental disorders diagnosed were schizophrenia (42%), substance related disorders (33%) and mental retardation (19%). The majority of offences were assault with intent to cause grievous bodily harm and malicious damage to property. This reflects the behaviour usually reported on by relatives of relapsed male Mental Health Care Users on admission to psychiatric hospitals or units in the Province. Of the witchcraft accusation offences 70% were committed by mentally ill mental health care users. CONCLUSION The majority of offenders referred for forensic observation had previous contact with the mental health services, yet 41 % of those Mental Health Care Users were found not mentally ill in relation to the alleged offence. Mopani District had the highest number of referrals who were found to be mentally ill. This finding needs to be further evaluated in terms of relationship to the effectiveness and accessibility of the Primary Health Care Service to Mental Health Care Users in Mopani.
Thesis (M.Med. (Psychiatry)) --University of Limpopo (Medunsa Campus), 2009
Keywords: Forensic observation; Offenders